1992
DOI: 10.1111/j.1365-2710.1992.tb01289.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of effect of codeine in the treatment of cough associated with acute upper respiratory tract infection

Abstract: Codeine is often used as a standard antitussive against which new antitussives are compared. However there is little information available about the effects of codeine on cough associated with upper respiratory tract infection. The present study investigated the effects of codeine syrup B.P. (30 mg/10 ml, q.d.s.) or syrup vehicle on cough frequency and the subjective severity of cough during a 3-h laboratory phase and a 4-day home phase of treatment. Cough frequency and subjective scores of cough severity were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
5

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 5 publications
1
34
0
5
Order By: Relevance
“…In contrast, Dicpinigaitis et al (1997) observed significantly greater suppression of capsaicininduced cough 2 hours after ingestion of 30 mg of codeine compared with placebo. In citric acid-induced cough, 20 mg of codeine was associated with significantly greater cough suppression than placebo (Empey et al, 1979) In two exemplary studies investigating cough due to URTIs, Eccles et al (1992) found that codeine at an initial dose of 30 mg, followed by 4 days of dosing at 30 mg four times a day, had no effect greater than placebo syrup, either on objective initial cough recording or on subsequent self-reported cough. In the second study by the same group, oral codeine (50 mg) was compared with placebo syrup in 82 subjects in a parallel group design using three measures of cough assessment (Freestone et al, 1996).…”
Section: Opiates: Codeine and Morphinementioning
confidence: 99%
“…In contrast, Dicpinigaitis et al (1997) observed significantly greater suppression of capsaicininduced cough 2 hours after ingestion of 30 mg of codeine compared with placebo. In citric acid-induced cough, 20 mg of codeine was associated with significantly greater cough suppression than placebo (Empey et al, 1979) In two exemplary studies investigating cough due to URTIs, Eccles et al (1992) found that codeine at an initial dose of 30 mg, followed by 4 days of dosing at 30 mg four times a day, had no effect greater than placebo syrup, either on objective initial cough recording or on subsequent self-reported cough. In the second study by the same group, oral codeine (50 mg) was compared with placebo syrup in 82 subjects in a parallel group design using three measures of cough assessment (Freestone et al, 1996).…”
Section: Opiates: Codeine and Morphinementioning
confidence: 99%
“…Having recruited a study population, there is an inevitable marked spontaneous regression back to normality. This, coupled with a particularly powerful placebo effect [165,166], makes the study of subjects with acute cough highly challenging. These factors, but particularly the daily variation in baseline, make crossover studies virtually impossible.…”
Section: Studies In Patientsmentioning
confidence: 99%
“…While there is evidence that placebo effects may play a part in the effectiveness of many antitussives (Eccles et al, 1992;Freestone & Eccles, 1997;Schroeder & Fahey, 2004;Taylor et al, 1993), this has not been studied systematically. A logical next step would be to examine placebo responses in patients with cough disorders.…”
Section: Limitations Of Experimental Methods and Future Directions Fomentioning
confidence: 99%
“…A number of recent double blind, placebo-controlled studies have shown that codeine is not significantly more effective than placebo in suppressing cough due to upper airway disorders (Bolser & Davenport, 2007;Eccles, Morris, & Jawad, 1992).…”
Section: Antitussive Medicationsmentioning
confidence: 99%
See 1 more Smart Citation